A Multipoint Problem for Pseudodifferential Equations - Klyus, I. S.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the well-posedness of a problem with multipoint conditions with respect to a chosen variable t and periodic conditions with respect to coordinates x 1,...,x p for equations unsolved with respect to the leading derivative with respect to t and containing pseudodifferential operators. We establish conditions for the unique solvability of this problem and prove metric assertions related to lower bounds for small denominators appearing in the course of its solution.